PENGARUH MODEL PROBLEM POSING SETTING KOOPERATIF TERHADAP PRESTASI DAN MINAT BELAJAR MATEMATIKA SISWA KELAS X SMA DI KABUPATEN MERAUKE DITINJAU DARI GAYA KOGNITIF SISWA - Tri Winihati, Irene Endah; Budiyono, Budiyono; Usodo, Budi (Jurnal Pembelajaran Matematika, 2014)
Abstract:  The aim of the research was to determine the effect of learning models on mathematics achievement and learning interest viewed from the student cognitive style. The learning models compared were conventional model, the setting cooperative learning model of Problem posing, and Problem Posing model. The type of the research was a quasi-experimental research. The population were the students of Senior High School in Merauke regency on academic year 2013/2014. The size of the sample was 213 students consisted of 71 students in control group, 71 students in the first experimental group and 71 students in the second experimental group. The instruments used were mathematics achievement test, quesioner, and Group Embedded Figure Test (GEFT). The data was analyzed using multivariate analysis of variance. The conclusions of the research were as follows.  (1) Both  the setting cooperative learning model of Problem Posing and Problem Posing learning model result in a better learning achievement than the conventional learning model, and the setting cooperative learning model of Problem Posing result in a better learning achievement than the Problem Posing learning model. (2) The conventional learning model, the setting cooperative learning model of Problem Posing, and Problem Posing learning model results in the same learning interest. (3) The   field independent students have a better learning achievement than the field dependent students. (4) The field independent students have a better learning interest  than the  field dependent students. (5) For the field dependent students, the setting cooperatif learning model of Problem Posing gives  better learning achievement than the Problem Posing model, and Problem Posing learning model gives better learning achievement than the conventional learning model, and the setting cooperative learning model of Problem Posing gives the same learning achievement with the Problem Posing model.  For the field independent students, the setting cooperative learning model of Problem Posing and the Problem Posing model gives  better learning achievement than the conventional learning model. (6) For the field dependent students, each learning models gives the same learning interest. For the field independent  students, each learning models gives the same learning interest.Keywords: Problem Posing,Setting cooperative, Learning achievement, learning interest, cognitive style.